TREATMENT OF TENDINITIS BY USING COLD THERAPY (ICE) IN HORSES. - Abdul Moniem Ibrahim Salih (Basrah Journal of Veterinary Research)
This study aimed to treat SDF tendonitis in the forelimbs of horses by application of cold therapy (ice) followed by controlled exercise program. The effect of this treatment was healing, disappearance of the pain and functional rehabilitation of the treated horses. (15) Working horses of varying breeds, sex, age (3-19) years suffering from acute superficial digital flexor tendonitis was used for this study from the beginning of September 2008 to the beginning of September 2010 in Kirkuk, Iraq. All the cases were followed up clinically. Swelling and thickness in the affected parts were measured during treatment period. Swelling was reduced after the treatment by the ice with significant variation (P< 0.05) in the (anterior-posterior and groove’s depth) aspects of sub-metacarpal bone area and (anterior-posterior) aspect of mid-metacarpal bone region. A significant variation (P